Effects of dietary exposure to ciguatoxin P-CTX-1 on the reproductive performance in marine medaka (Oryzias melastigma). (March 2020) - Yan, Meng; Mak, Maggie Y.L.; Cheng, Jinping; Li, Jing; Gu, Jia Rui; Leung, Priscilla T.Y.; Lam, Paul K.S.
Abstract: Ciguatoxins are natural compounds produced by benthic dinoflagellates Gambierdiscus and Fukuyoa spp., which cause fish intoxication by ciguatera fish poisoning. This study aimed to assess the dietary exposure effects of ciguatoxin P-CTX-1 on the reproductive performance in marine medaka ( Oryzias melastigma ). Fish which ingested >1.16 pg·day −1 for 21 days exhibited abnormal behaviors including diarrhea, abnormal swimming, loss of appetite and decreased egg production. After 7-day exposure to P-CTX-1 at a dose of 1.93 pg·day −1, significant gender-specific differences in reproductive performance and decreased hatching rate of the offspring were observed. Chemical analysis of P-CTX-1 showed that the P-CTX-1 accumulation rates were 24.1 ± 1.4% in female fish and 9.9 ± 0.4% in male fish, and 0.05 pg·egg −1 was detected. The results illustrate that dietary exposure to P-CTX-1 affected the reproductive performance and survival of offspring, and caused bioaccumulation and maternal transfer of P-CTX-1 in marine medaka. Highlights: Bio-encapsulation of ciguatoxin P-CTX-1 was applied for dietary exposure in medaka Exposure to P-CTX-1 caused abnormal behaviors and decreasing egg production. Gender-specific differences on the reproductive performance. The offspring from P-CTX-1 treated parents suffered from hatching failure. Bioaccumulation and maternal transfer of P-CTX-1 were observed in marine medaka fish.